Analisis Produktivitas Alat Berat Pada Pekerjaan Peningkatan Jalan Batas Kota Pegaf – Batas Kabupaten Manokwari Selatan - Ivanka Thamara Victorya Bannegau, Rivelya; Bahtiar Bahtiar; Helen G. Wayangkau (Jurnal Sipil Terapan, 2024)
Roads in Manokwari City still need a lot to be improved, especially on the Pegaf city boundary road - South Manokwari district, because this road connects the border between the City and the district.... This study aims to calculate the productivity of heavy equipment working on road improvement work, Analyzing the balance of road improvement work tools and knowing the total cost and time required in road improvement projects. So that this research is expected to be useful for optimizing the performance of road sections and being able to provide solutions to problems that occur and can provide an overview of the process of using heavy equipment that is effective and efficient. Productivity is the ability to produce something, so it can be said that heavy equipment productivity is the ability of heavy equipment to produce something per unit of time. In general, heavy equipment work production has the same calculation principles. The basic principles of calculating heavy equipment work production are 4 steps, namely calculating actual capacity, cycle time, calculating gross work production (PKK) and calculating actual work production (PKA). So it can be concluded that the productivity of ordinary embankment excavator 173.68m3 / hour, dump truck 10 tons of ordinary embankment 45.58m3 / hour, optional embankment 36.3m3 / hour, asphalt foundation layer (HRS Base) 7.91m3 / hour, Dump truck 4 tons of Class A aggregate layer 4.02m3 / hour, Class B aggregate layer 4.06m3/hour, motor grader 315m2/hour regular embankment, 174.30 m3/hour optional embankment, 561m2/hour pavement preparation, Class A aggregate layer 274.63m3/hour, Class B aggregate layer 274.63m3/hour, vibratory roller regular embankment 159.36 m3/hour, class A aggregate layer 77.02m3/hour, class B aggregate layer 77.02m3/hour asphalt distributor binder layer 4980 liters, air compressor binder work 1365.35 liters, asphalt finisher asphalt foundation layer (HRS Base) 69.85 tons, tandem roller regular embankment 39.84m3/hour, preparation of the road body 272.98m3 / hour, paving 86.59m3 / hour, wheel loader preferred embankment 117.58m3 / hour, class A aggregate layer 114.98m3 / hour, class B aggregate layer 116.53m3 / hour and tire roller paving 104.06 tons and the total cost of all equipment rental is Rp. 254,091,569.